Paired Variation Training on Passing Ability in Futsal Game - Akbar Maulana Budiman; Akhmad Sobarna; Hendya Alif Junanda (STKIP Pasundan Press, 2025)
Sport has an important role in human life, including in the development of motor skills and teamwork. This study aims to determine the effect of paired variation training on passing ability in futsal games. The method used was experimental research with a pretest and posttest design on a single group. The results showed that the application of the paired variation training method had a significant effect on improving passing ability, with an average pretest value of 12.60 and a posttest of 17.65, and an average increase of 5.05 points (± 40.1%). The paired sample T-test produced a significance value of 0.001 <0.05, which showed a significant difference between the pretest and posttest. Paired variation training not only improves technical skills, but also provides a contextualized and applicable training experience, involving communication and cooperation between players. This research contributes to the development of sports training methods, especially in improving basic passing techniques for futsal extracurricular students at the student level.